The Frequency of H. Pylori Infection Among Patients Experiencing Digestive Endoscopy a Multi Center Study - Naeem Jan, Atta Muhammad Khan, Muhammad Iltaf (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The development of endoscopy, particularly gastroscopy, has changed the diagnosis of oeso-gastroduodenal disorders. there is little information accessible on the methods of intestinal endoscopy. Objective: The study's goal was to evaluate the pathologic diagnosis of endoscopic lesions and the presence of H. pylori during endoscopy (digestive examination). Methodology: 100 patients participated in the study, and there were 42 men and 58 women in it. This Multi center study was done department of gastroenterology and medical department hmc and lrh Peshawar between May 2022 and November 2022. The patients freely signed the permission form after being made informed of the goal. The data from each patient's gastrointestinal endoscopy were gathered for analysis. The research was authorized by the ethics and review committees of our institute's teaching hospital. The patients who had gastrointestinal endoscopies were included in this study by the inclusion criteria. Results: According to data, more female patients than male patients sought medical treatment for this problem. It was also observed that patients under the age of 45 comprised a greater percentage of the patient group than patients over the age of 45. Epigastralgia, which was reported by 72% of patients, was the most frequent sign and symptom, according to the data. Vomiting was the next most prevalent symptom, followed by gastrointestinal bleeding and weight loss. Several patients simultaneously reported many of these symptoms. Esophageal varices were shown to be associated with males, with a significant p-value of 0.045, it was discovered. The H. pylori-related gastritis was connected to a lesion. Conclusion: The study's objective was to determine the prevalence of H. pylori infection and the characteristics of endoscopic lesions in patients having gastrointestinal endoscopies. Analysis was done to determine the impact of different endoscopic lesions on various demographic parameters in this retrospective study. Age and stomach tumors were shown to be connected, and smoking may have had some influence on the development of peptic ulcers. And the majority of patients had an upper gastrointestinal endoscopy regularly. Keywords: H. Pylori infection, digestive endoscopy,